Ultra-high Curie temperature (>800 °C) low sintering temperature Bi2(1−x)La2xWO6 piezoelectric material for the applications of seafloor hydrothermal vents detection. (16th September 2016) - Liao, Qingwei; An, Zhao; Huang, Haining; Fang, Mingwei; Chen, Zhongjun; Peng, Shasha; Li, Kun
Abstract: Searching low sintering temperature material with ultra-high Curie temperature (>800 °C) is urgent to seafloor hydrothermal vents detection. Bi2 WO6, as the simplest member of the Aurivillius family was improved to possess ultra-high Curie temperature and ultra-high depolarization temperature by experiment at first time. The crystal structure was determined by ab initio and Rietveld refinement calculations. The symmetry group of ultra-high Curie temperature Bi2 WO6 is Aba2 (41). The Curie temperatures of Bi2(1−x) La2x WO6 (x = 0, 0.005, 0.01, 0.02, 0.04) with increasing x are 952 °C, 1008 °C, 905 °C, 853 °C, 822 °C, respectively, and depolarization temperatures of them are around 915 °C, 905 °C, 880 °C, 800 °C, and 725 °C, respectively. The typical properties are as follows: Curie temperature T c = 905 °C, depolarization temperature T d = 880 °C, mechanical quality factor Q m = 621.8, d 33 = 17 pC/N, K 33 = 82.01, tan δ = 0.19 × 10 −2 with x value of 0.01.